2003
DOI: 10.1111/1464-0597.00153
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Behavior's Dependency on Different Forms of Knowledge

Abstract: Cet article présente trois raisons pour lesquelles l'influence de la connaissance sur le comportement écologique est systématiquement sous-estimé. Tout d'abord, ce n'est pas la simple masse de connaissances disponibles que déter-mine le comportement: différentes formes de connaissances doivent converger pour favoriser le comportement écologique. Ensuite, l'impact de la connaissance n'est pas détecté parce que certaines procédures statistiques ne contrôlent pas les erreurs de mesure ni ne révèlent avec précisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
287
1
24

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(358 citation statements)
references
References 63 publications
15
287
1
24
Order By: Relevance
“…The convergence of all of these forms is, for some authors, a necessary-though not sufficient-condition for ecological behaviour [4] and it is mediated by attitude and intention [30] when explaining behaviour. The current taxonomies of value, which are not related to specific objects or behaviours, mainly refer to unstable decision-making, largely depending on context and the salience of information when action is implemented.…”
Section: Habitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The convergence of all of these forms is, for some authors, a necessary-though not sufficient-condition for ecological behaviour [4] and it is mediated by attitude and intention [30] when explaining behaviour. The current taxonomies of value, which are not related to specific objects or behaviours, mainly refer to unstable decision-making, largely depending on context and the salience of information when action is implemented.…”
Section: Habitsmentioning
confidence: 99%
“…However, personality traits are thought to influence travel Although knowledge shows, empirically, a low correlation with behaviour and, notably, with sustainable behaviour [28], it does correlate with intention when situational constraints are taken into account [29] and its effect relies more probably on the synergy of its different forms (declarative, procedural, effectiveness and social, Table 1) that can enhance or inhibit each other. The convergence of all of these forms is, for some authors, a necessary-though not sufficient-condition for ecological behaviour [4] and it is mediated by attitude and intention [30] when explaining behaviour. The current taxonomies of value, which are not related to specific objects or behaviours, mainly refer to unstable decision-making, largely depending on context and the salience of information when action is implemented.…”
Section: Habitsmentioning
confidence: 99%
“…While behavior scientists have proposed a variety of useful frameworks for explaining individual action, we chose to use a framework proposed by Kaiser and Fuhrer (2003) that centers on four different domains of knowledge as an organizational tool: declarative (factual/technical socioecological information), procedural (how-to information and skills), effectiveness (subjective understanding of impacts/efficacy), and social (subjective understanding of normative trends and social expectations) (Redman, 2013;Kaiser & Fuhrer 2003). While the knowledge domains are insufficient individually to entirely explain the motivations behind people's actions, they collectively provide an overarching framework for integrating an array of behavioral theories (Frisk & Larson, 2011).…”
Section: Knowledge Domainsmentioning
confidence: 99%
“…Declarative knowledge typically addresses how environmental systems operate in factual, technical, mechanical or biophysical terms, such as information about the ecological structure, functioning of ecosystems, and social-ecological interactions (Kaiser & Fuhrer, 2003). Although research has suggested that this is the least effective type of knowledge in promoting pro-environmental behaviors, most educators focus on disseminating declarative knowledge (Pooley & O'Connor, 2000a;Simmons & Volk, 2002).…”
Section: Knowledge Domainsmentioning
confidence: 99%
“…Assim, pode-se ter como recomendação para elaboração de um framing positivo mais eficaz a manipulação das variáveis que sustentam um ELOC interno, em sua porção contexto-dependente, não apenas como medida de personalidade. O uso de responsabilização como estratégia parece promissor, inclusive, contando com a associação demonstrada nos Psico (Porto Alegre), 2017; 48(4), 306-316 resultados entre esse tipo de estratégia e a indicação de comportamento, em acordo com a recomendação de apresentação de conhecimento procedural para promover o comportamento pró-ambiental (Kaiser & Fuhrer, 2003). Por sua vez, o uso de mensagens normativas é reconhecidamente eficaz na promoção de comportamento pró-ambiental (Cialdini, 2011).…”
Section: Discussionunclassified